2016
DOI: 10.1186/s12885-016-2803-2
|View full text |Cite
|
Sign up to set email alerts
|

With or without reirradiation in advanced local recurrent nasopharyngeal carcinoma: a case–control study

Abstract: BackgroundThe study aimed to evaluate the long-term outcome in patients with advanced local recurrent nasopharyngeal carcinoma (NPC) treated with or without reirradiation.MethodsA total of 44 patients treated without reirradiation (non-RT + chemotherapy) were matched with 44 patients treated with reirradiation (re-RT+/-chemtherapy) by age, sex, Karnosky performance score (KPS), rT stage, rN stage, and time interval between initial radiation and recurrence (TI). Overall survival (OS) rate and time to progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Although surgery or re-RT is the only chance to cure, the survival outcomes of palliative chemotherapy may not be worse than 'curative' treatment. A case-matched, retrospective study showed equivalent OS for patients received re-RT and chemotherapy alone (13). As expected, more RT-induced mortalities were observed in the re-RT group and more deaths due to local recurrence were observed in the chemotherapy alone group.…”
Section: Palliative Chemotherapy Alone May Not Be a Bad Alternativesupporting
confidence: 62%
“…Although surgery or re-RT is the only chance to cure, the survival outcomes of palliative chemotherapy may not be worse than 'curative' treatment. A case-matched, retrospective study showed equivalent OS for patients received re-RT and chemotherapy alone (13). As expected, more RT-induced mortalities were observed in the re-RT group and more deaths due to local recurrence were observed in the chemotherapy alone group.…”
Section: Palliative Chemotherapy Alone May Not Be a Bad Alternativesupporting
confidence: 62%
“…Among the patient groups with recurrent stage III and IVA/IVB disease, 52.1% and 41.2% were treated with re-RT, respectively. However, in a case-matched retrospective study, similar survival outcomes were observed for patients who received re-RT vs chemotherapy alone, 22 and the latter was inevitably associated with fewer RT-related toxicities. However, despite a numerical 10% survival advantage, our data showed that re-RT was only marginally better than chemotherapy alone (5-year OS 21.8% vs 11.6%; P = .06), and it was likely attributed to the high rates of life-threatening late toxicities (grade 4:22.9%; grade 5:17.7%).…”
Section: Discussionmentioning
confidence: 67%
“…[10][11][12] Our analysis suggests that age and rGTV volume were the most important parameters for OS. However, in a case-matched retrospective study, similar survival outcomes were observed for patients who received re-RT vs chemotherapy alone, 22 and the latter was inevitably associated with fewer RT-related toxicities. We believe that chemotherapy alone might be regarded as a reasonable alternative for patients with adverse prognostic factors, especially those with extensive local recurrence.…”
Section: Discussionmentioning
confidence: 67%
“…Our group launched the rst case-control study to compare the survival of rT3-4 lrNPC patients treated with reirradiation or PCT alone and found that patients in these two groups achieved similar OS [26]. However, You et al established a new surgical system and veri ed that a combination of aggressive reirradiation could further enhance OS compared with PCT alone [27].…”
Section: Discussionmentioning
confidence: 99%